Relationship Between Nasal Congestion and Learning Concentration in Medical Student - Yogi Agustian Nugroho; Andriana Tjitria Widi Wardani Sardjana; Agung Sulistyanto; Iwang Yusuf; Kamilia Dwi Utami (Universitas Islam Sultan Agung, 2025)
Allergic Rhinitis is not a fatal disease, but it can affect a person's quality of life and interfere with work, including their ability to learn. One of the most frequently complained of symptoms of allergic rhinitis is a blocked nose. The worldwide prevalence of allergic rhinitis affects between 10%-30% of the population. The aim of this study was to determine the relationship between nasal congestion and learning concentration allergic rhinitis sufferers among FK UNISSULA students, Class of 2022.This research is an observational study with a cross sectional design with the sample criteria being students of FK Unissula Class of 2022 and 2023 who suffer from allergic rhinitis and meet the inclusion and exclusion criteria. The inclusion criteria in this research were students of FK Unissula Class of 2022 and 2023 and were willing to be research subjects. The exclusion criteria in this study were students with anatomical nasal abnormalities and those experiencing chronic rhinosinusitis with or without nasal polyps, deviated septum, adenoid hypertrophy, and neoplasms.There were 50 respondents from Unissula Medical Faculty students who suffered from allergic rhinitis. It was found that 38 (76%) students had a blocked nose and 12 (24%) students did not experience a blocked nose. The research results showed that the majority of students experienced severe nasal congestion and the majority of students had good concentration on their studies. The results of the analysis of the relationship between nasal congestion and learning concentration in allergic rhinitis sufferers using the Spearman test obtained p 0.000 with a correlation coefficient of 0.538.The results of the analysis above showed that there was a significant relationship between nasal congestion and learning concentration in allergic rhinitis sufferers.